Specific Features of the Process of Teaching a Foreign Language - Rustamova, Shoxista (The Lingua Spectrum, 2025)
The process of teaching a foreign language represents a complex, dynamic, and multidimensional pedagogical activity aimed at developing students’ communicative competence and intercultural awareness. Unlike the traditional grammar-translation approach, modern foreign language teaching emphasizes the practical use of language in real-life contexts. Teachers employ communicative, interactive, and student-centered methods that encourage learners to participate actively in the learning process. This includes the integration of technologies such as multimedia resources, online platforms, and authentic materials that reflect the cultural and social realities of the target language community. An effective foreign language classroom combines linguistic, sociolinguistic, and pragmatic components, allowing students to master not only grammar and vocabulary but also appropriate language use in various communicative situations. The teacher’s role has transformed from being a transmitter of knowledge to a facilitator and guide who creates meaningful learning experiences through project work, role-playing, discussions, and collaborative tasks. Special attention is given to motivation, individual learning styles, and differentiated instruction, ensuring that every learner progresses according to their potential. Moreover, foreign language education promotes intercultural competence, helping learners understand the values, traditions, and communication patterns of other nations, which in turn fosters tolerance and global awareness. By harmoniously developing the four main language skills – listening, speaking, reading, and writing – students acquire not only linguistic knowledge but also the ability to think and communicate effectively in the target language. Ultimately, the process prepares learners to function confidently and appropriately in multicultural environments.